2012
DOI: 10.1101/lm.025908.112
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter knockout rats show improved strategy set-shifting and reduced latent inhibition

Abstract: Behavioral flexibility is a cognitive process depending on prefrontal areas allowing adaptive responses to environmental changes. Serotonin transporter knockout (5-HTT−/−) rodents show improved reversal learning in addition to orbitofrontal cortex changes. Another form of behavioral flexibility, extradimensional strategy set-shifting (EDSS), heavily depends on the medial prefrontal cortex. This region shows functional changes in 5-HTT−/− rodents as well. Here we subjected 5-HTT−/− rats and their wild-type coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…In addition, low levels of perseveration were also associated with increased 5-HT 2A receptor binding in the mOFC and lOFC. Whilst prior studies have demonstrated a role for 5-HTT (Holmes and Fam, 2013;Nonkes et al, 2012) and striatal DAergic mechanisms in reversal learning performance (Clarke et al, 2011;Collins et al, 2000;O'Neill and Brown, 2007), we found no evidence of abnormalities in binding at 5-HTT in highor low-perseverative rats nor any alterations in several key indices of DA transmission in the DMS. These findings indicate that natural variation in serotonergic tone and MAO-A and MAO-B gene expression in the OFC and DRN, together with reduced TPH2 mRNA expression in the DRN, may underlie poor spatial-discrimination reversal learning in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, low levels of perseveration were also associated with increased 5-HT 2A receptor binding in the mOFC and lOFC. Whilst prior studies have demonstrated a role for 5-HTT (Holmes and Fam, 2013;Nonkes et al, 2012) and striatal DAergic mechanisms in reversal learning performance (Clarke et al, 2011;Collins et al, 2000;O'Neill and Brown, 2007), we found no evidence of abnormalities in binding at 5-HTT in highor low-perseverative rats nor any alterations in several key indices of DA transmission in the DMS. These findings indicate that natural variation in serotonergic tone and MAO-A and MAO-B gene expression in the OFC and DRN, together with reduced TPH2 mRNA expression in the DRN, may underlie poor spatial-discrimination reversal learning in rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The associative learning phenomena of latent inhibition – where previous exposure to a non-reinforced cue blunts future conditioning to that cue – has also been proposed to play a role in behavioral flexibility (Chess et al, 2012; Nonkes et al, 2012). Blunted latent inhibition may increase exploration of previously irrelevant rule sets during a strategy shift that could lead to an apparent facilitation of shifting.…”
Section: Resultsmentioning
confidence: 99%
“…A separate cohort of 32 rats were divided into 4 groups (n=8/group) to test the interaction between drug history (CTA vs air) and cue pre-exposure (pre exposed, “PE” vs non pre exposed, “NPE”) on classical conditioning using a procedure based on Nonkes et al (2012). CTA and air-treated rats were acclimatized to SCM one day before training began (see 2.3.1).…”
Section: Methodsmentioning
confidence: 99%
“…Extracellular 5-HT level is 5-10 fold increased in striatum, cortex and substantia nigra of 5-HTT-KO mice (Mathews et al, 2004) suggests importance of this model in studying 5-HT effects in different behavioral paradigms A reduced 5-HT level in 5-HTT-KO rodents resulted in improved performance in reversal learning (Brigman et al, 2010). A study by Nonkes et al, using Extra-dimensional Strategy Set-shifting (EDSS) task has reported HTT-/-rats showed improved strategy shifting and reduced latent inhibition, indicating that HTT has effects on attention and cognitive process (Nonkes et al, 2012).…”
Section: Serotonin Transporter Knock-out (5htt-ko) Rodentsmentioning
confidence: 94%